Forensic characteristics and population genetics of Chinese Kazakh ethnic minority with an efficient STR panel - Chong Chen; Yuxin Guo; Xiaoye Jin; Wei Cui; Yuanyuan Wei; Yating Fang; Qiong Lan; Tingting Kong; Tong Xie; Bofeng Zhu (PeerJ, 2019)
On the purpose of enhancing the forensic efficiency of CODIS STR loci, new STR loci have been gradually discovered and developed into some commercial multiplex systems. Recently, 22 STR loci including 18 non-CODIS STR loci and four CODIS STR loci were investigated in 501 unrelated healthy individuals of Kazakh ethnic group. Seven to 20 alleles at the different loci were identified and altogether 276 alleles for 22 selected loci were detected with the corresponding allelic frequencies ranging from 0.0010 to 0.3623. No significant deviation was observed from the Hardy–Weinberg equilibrium test for any of the 22 STRs. The value of cumulative power of discrimination in Kazakh group was 1-1.00E−28. Analyses of population differentiations and genetic distances between Kazakh and other Chinese groups presented that the Kazakh group with the Uygur group. These 22 STR loci evenly distributed on 22 different autosomal chromosomes were characterized by high genetic diversities and therefore could be utilized in the forensic cases to further increase the discrimination performance.